Cost Benefit Analysis the Participation of Indonesia in Asia Region Funds Passport - Syadullah, Makmun; Ardiansyah, Benny Gunawan (International Journal of Economics and Financial Issues, 2017)
APEC Finance Ministers' Forum initiated the Asia Region Funds Passport (ARFP), a framework of multilateral cooperation to facilitate cross-border fund market. ARFP is the concept of cross-border distribution and operation of collective investment schemes. Indonesia is expected to join in this framework. This study attempted to elaborate the cost and benefit of joining this framework from Indonesia's perspective. We conclude that Indonesia could get some benefit to elevate it's economic, however, there are a few potential disadvantages. On the other hand, there are also some constraints, particularly the domestic rules including capital market act and tax regulation. Indonesia needs to adjust that regulation and it requires enormous efforts and quite long period. We recommended two options: First, join earlier and Indonesia would have a chance to propose some inputs in the ARFP regulation draft and keep its interest on the track. The second option, Indonesia doesn't need to join the ARFP. But, the government have to adjust its basic regulation. Indonesia must develop its mutual fund's industry, so it could compete in the global market. The most important thing is adjusting some articles in the capital markets act, so it could open branches in other countries. Keywords: ARFP, Fund Passpord, Mutual Fund, APEC, Cost Benefit JEL Classifications: F38, G23